Arsenic Contamination in Groundwater of Punjab - An Overview - Kaur, Prabhdeep; Singh, Inderpreet; Kaur, Paramjeet (IJRDO-Journal of Applied Science, 2015)
Groundwater is a common pool resource for drinking and irrigation purposesin Punjab and can be drawn on demand wherever and whenever needed. Pollution by varioustoxic chemicals is posing a great problem nowadays and contamination of arsenic ingroundwater is estimated to affect various parts of the country especially near the gangeticfluvial plains of India including Punjab. As is found to be carcinogenic, As(III) is more toxicthan As(IV). In this study, overview of the contamination of arsenic in groundwater of Punjabis studied. It is found that a number of areas have been affected with As contamination thatexceeds the standard given in BIS(2012). Being an agricultural state it becomes even moreimportant to identify and curb the problem of As contamination in Punjab.